The relationship between digital technologies and innovation: A review, critique, and research agenda - Hao Jiao; Tang Wang; Dirk Libaers; Jifeng Yang; Lingshu Hu (Journal of Innovation & Knowledge (JIK), 2025)
Digital technologies (DTs) have resulted in innovations that have fueled global knowledge-based economic development. This systematic review of the literature focuses on the relationship between DTs and innovation. Drawing on the extant literature, we investigate 685 articles published in 41 journals from 1997 to 2023. We present the current state of different types of articles and the theoretical perspectives applied in the previous research. Based on topic modeling analyses and interpretations of existing work, we develop a meta-framework that distinguishes between the direct and indirect effects of DTs on innovation and considers four levels of potential heterogeneity affecting the relationship. Finally, we propose an agenda that emphasizes the avenues for future research on DTs and innovation.
Keywords: O33; 650; Digital technologies; Innovation; Multilevel framework; New product development